Is Community Tourism good? : Challenges and Perspectives of Prainha do Canto Verde, Ceará, Northeast Brazil. - Gorayeb, Adryane; Dantas Coelho, Susana (RITUR - Revista Iberoamericana de Turismo, 2023)
The research aimed to evaluate community tourism in the Resex of Prainha do Canto Verde, Ceará, Brazil, located about 130 km east of the capital, Fortaleza. The analysis was carried out using a qualitative approach, applying the Inventory of the Tourist Offer (INVTUR) and interviews with representatives of the municipal government, non-governmental organizations and local community associations, based on the concepts proposed by Irving (2009). It was found that community tourism is not perceived as the main source of income for families in the community, but it interacts with traditional activities (fishing and agriculture), in addition to covering cultural, social and environmental issues of the locality, in a context in which it does not involve the community as a whole, in its decision-making and participatory processes. On the other hand, the absence of infrastructure for the development of a more competitive tourist offer, in a traditional model, denotes relevance to community tourism, which influences the polarization of relations and economic interests present in the daily life of the community, manifested in the performance of two associations of residents with discordant ideals and actions. This study can contribute to the planning of tourist activities in the community and in similar scenarios, with a view to better tourism management and more sustainable development, involving tourists, governments and the local population.